Studi Karakteristik Campuran Aspal Beton Lapis Aus (AC-WC) Menggunakan Aspal Penetrasi 60/70 dengan Penambahan Lateks - Thanaya, I Nyoman Arya; Puranto, I Gusti Raka; Nugraha, I Nyoman Sapta (Department of Civil Engineering, Diponegoro University, 2016)
Asphalt on pavement in long term may undergo hardening, so it needs addition of additive that can make it remain flexible. This experiment tried to produce asphalt concrete wearing course (AC-WC) using asphalt penetration 60/70 with the addition of latex, with aim to know the characteristic of AC-WC mix at the optimum of asphalt content with addition of latex in variation of 0%, 2%, 4%, 6%, 8%, and 10% of the total binder. Latex was initially mixed with the asphalt, then the aggregates were proportioned based on ideal grading. The samples were produced in hotmix process. The density of latex was found 0.977 with dry rubber content of 61.95%. The optimum of asphalt content that was 5.7%, where all Marshall characteristics were met. It was chosen the mix with 4% latex by total binder where all properties of asphalt binder were still met. It was obtained that the Stability value was 1439.26 kg (≥ 800 kg), Flow 3.84 mm (2-4 mm), Marshall Quotient 379.66 kg / mm (≥ 250 kg / mm), VIM 4.437% (3-5%), VMA 15.280% (≥ 15%), VFB 70.961 (≥ 65%). The mixture that contains latex had better resistance to deformation under dynamic creep loading at 40 °C.